YOGA PADA PANCATANTRA INDIA DAN KALADESA PADA TANTRI KAMANDAKA JAWA KUNO: KAJIAN SASTRA BANDINGAN - Ambar Andayani (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2010)
ABSTRACT.Â  Indian Pancatantra is the archetype of Old Javanese Tantri Kamandaka, Laos Tantrai and Siam Tanthai. This research wants to compare between Pancatantra and Tantri Kamandaka which comes from two different countries in the same continent, Asia, and from different periods (200 BC and 1200â€™s). This comparative literary study shows that they produce local colors. These local colors are analyzed with Thompsonâ€™s motif and Riffaterreâ€™s semiotic which is conducted by heuristic and hermeneutic levels. Through the applications of interpretation and interdisciplinary literature, the symbols found in the folktales are explained. The comparison of both fables achieves the authentic meanings, â€œA Louse and A Bugâ€ in Indian Pancatantra modifies Yoga and â€œA Louse and A Bugâ€ in Old Javanese Tantri Kamandaka tells about Kaladesa. Finally the transformation from yoga into kaladesa is investigated with the concept of acculturation.Key words: comparative literature, motif, symbol, yoga, kaladesa